Effect of Loan Defaults on the Profitability of Nepalese Commercial Banks - Tamrakar, Ashna (Nepalese Journal of Finance, 2024)
The study examines the effect of loan defaults on the profitability of Nepalese commercial banks. The dependent variables selected for the study are return on equity and return on assets. The selected independent variables are bank size, interest spread rate, loan loss provision, non-performing loan, capital adequacy ratio, and credit-to-deposit ratio. The study is based on secondary data of 15 commercial banks with 105 observations for the study period from 2016/17 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of loan defaults on the profitability of Nepalese commercial banks. The study showed that interest spread rate has a positive impact on return on assets and return on equity. It implies that increase in interest spread rate leads to increase in return on assets and return on equity. In addition, capital adequacy ratio has a positive impact on return on assets and return on equity. It indicates that increase in capital adequacy ratio leads to increase in return on assets and return on equity. However, nonperforming loan has a negative impact on return on assets and return on equity. It implies that increase in nonperforming loan leads to decrease in return on assets and return on equity. Moreover, loan loss provision has a negative impact on return on assets and return on equity indicating increase in loan loss provision leads to decrease in return on assets and return on equity. Furthermore, bank size has a positive impact on return on assets and return on equity. It means that increase in bank assets size leads to increase in return on assets and return on equity.